Promoting Breastfeeding and Interaction of Pediatric Associations With Providers of Nutritional Products - Bognar, Zsolt; De Luca, Daniele; Domellöf, Magnus; Hadjipanayis, Adamos; Haffner, Dieter; Johnson, Mark; Kolacek, Sanja; Koletzko, Berthold; Saenz de Pipaon, Miguel; Shingadia, Delane; Tissieres, Pierre; Titomanlio, Luigi; et al. (Frontiers in Pediatrics, 2020)
Paediatric associations have been urged not to interact with and not to accept support from commercial providers of breast milk substitutes (BMS), based on the assumption that such interaction would lead to diminished promotion and support of breastfeeding. The leadership of seven European paediatric learned societies jointly reviewed the issue and shares the conclusions here. We consider breastfeeding the best way of infant feeding and strongly encourage its active promotion, protection and support. We support the WHO Code of Marketing of BMS. Infant formula and follow-on formula for older infants should not be advertised to families or the public to reduce the risk of undermining breastfeeding. With consistently restricted marketing of BMS, families need counselling on infant feeding choices by well-informed paediatricians. Current and trustworthy information is shared through congresses and other medical education directed and supervised by independent paediatric organisations or public bodies. Financial support from commercial organisations for congresses, educational and scientific activities of paediatric organisations is an acceptable option if adequate scientific, ethical, societal and legal standards are followed, any influence of commercial organisations on the programme is excluded, and transparency is ensured. Public-private research collaborations for improving and evaluating pharmaceuticals, vaccines, medical devices, dietetic products and other products and services for children are encouraged, provided they are guided by the goal of enhancing child health and are performed following established high standards. Investment of public funding for research aiming at promoting child health and for medical education should be strengthened.